Hybrid harmonic‐intermodulation distortion behavioral model for shortwave power amplifiers. Issue 7 (14th March 2019) - Xu, Gaoming; Liu, Taijun; Ye, Yan; Zhang, Xiupu
Abstract: In this article, a hybrid harmonic‐intermodulation distortion (HHIMD) behavioral model is proposed for imitating the shortwave power amplifier (SWPA) behavioral distortion, that is, harmonic distortion, intermodulation distortion, and memory effect. The proposed model is composed of an intermodulation distortion module, a quadrature digital up‐converter module and a harmonic distortion module. To demonstrate the modeling accuracy, the proposed model and measured SWPA are compared in the time domain and spectrum domain. It is shown that the proposed model can imitate the SWPA not only harmonic and intermodulation distortion, but also memory effect. The modeling normalized mean squared error between the HHIMD and measured SWPA output is lower than −44‐dB.